AN INTRODUCTORY STUDY ON DALALAH IN ISLAMIC EPISTEMOLOGICAL LAW - Muhammad Amin Nasution (TAQNIN: Jurnal Syariah dan Hukum, 2023)
ABSTRACTUsul Fiqh is a branch of science that until now the benchmark in the process istinbath Islamic law. If traced its history, we all know that the birth, growth and development of Usul Fiqh legal problems began when Muslims dynamics continue to evolve with the times. Hence, the necessary process of Ijtihad, to give a definite legal status of the legal problems at the time of the Prophet Muhammad was not found practical, and yet thrive in this modern era. The practice of marriage through a video conference, euthanasia, in vitro fertilization, cloning humans, a few of the many problems facing people today, which requires rule of law so that the Muslim community is maintained their religiousity from the things forbidden by Allah May He be elevated. Of the many objects in the study of Usul Fiqh, Studies on dalalah an interesting study once seized the attention of students of Islamic law. Dalalah are actually a lot more load semiotic language debate in the Qur'an and hadith and technical rules, it has strict rules and procedural processes in the context of Islamic law istinbath process. In fact, differences of opinion among Islamic scholars pretty much due to the differences in the language of semiotics in understanding the Qur'an and Hadith. On the basis of these considerations and perspectives, the authors assess the discourse surrounding derivatives dalalah and technical rules becomes very important to know though in its concise approach. Key Word : Dalalah, Ushul Fiqh, Semiotic, Ijtihad